An African perspective on gender and adjustment issues in firms' entrepreneurial orientation (2011)
The paper reviewed earlier attempts that consider female and males on entrepreneurial development. A specific contextual difference in their reaction to cultural expectations in organizational practices and entrepreneurial traits was considered from African perspective which has not enjoyed much attention in entrepreneurial adjustment discussions. The paper revealed that certain cultural practices reinforced by stereotype largely determine the difference between male and females' adjustment to a firm's entrepreneurial orientation. This necessitated the proposition that men and-women would differ in their adjustment to the dimensions of entrepreneurial orientation, especially in an African country. A major conclusion reported in the paper is that any firm that seek to promote entrepreneurial orientation need to consider the employees adjustment as an important variable